Jim Carruthers and Mr. Jones - (Author); (Interviewer); (Publisher) (1930)
Photograph - Jim Carruthers and Mr. Jones (Fire Ranger) on a boat with their catch of fish at Pelican Portage, Alberta. A note on back reads: Jim Carruthers disappeared without any trace in spring, 1935. Drowned in Athabasca river. Probably fallen from his raft